2022
DOI: 10.3389/fmars.2022.711174
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri)

Abstract: Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The NFPs inhabit the east Asian coast, a geographic hotspot of anthropogenic threats (Walther et al., 2020; Xiong et al., 2018; Yuen et al., 2023). Rapidly growing anthropogenic activities are influencing NFPs in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NFPs inhabit the east Asian coast, a geographic hotspot of anthropogenic threats (Walther et al., 2020; Xiong et al., 2018; Yuen et al., 2023). Rapidly growing anthropogenic activities are influencing NFPs in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Kyphoscoliosis in cetaceans is typically reported through in situ visual assessments during photo-identification field studies (Bertulli et al, 2015), and more subtle abnormalities are discovered during necroscopic examinations (DeLynn et al, 2011). As part of the pioneering stranded cetacean imaging programme in the Republic of Korea, NFPs stranded in Korean waters have been routinely assessed using post-mortem computed tomography (PMCT) to provide initial screening and supplementary evidence for conventional necropsy (Yuen et al, 2022(Yuen et al, , 2023. This case report presents the first documented cases of congenital, degenerative and traumatic kyphoscoliosis in two NFPs using PMCT.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of a dead organism, obtaining information regarding clinical symptoms becomes impossible. In the present study, our group adopted the PMCT workflow and imaging parameters with reference to Yuen et al [9,10] for the diagnosis of abdominal gas embolism and upper aerodigestive tract obstruction. We found that mesenteric fibrosis was a significant radiological sign to propose the presence of intestinal adhesion, which was confirmed via necropsy.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the underlying pathogenesis of this disease in cetaceans is still not fully understood. To seek better understanding of the causes of death and underlying pathology, cetaceans stranded in South Korean waters have been routinely assessed using post-mortem computed tomography (PMCT) to provide additional information complementing the findings of conventional necropsy [9,10]. In this case report, we present a case of ABO in a stranded narrow-ridged finless porpoise and demonstrate the relevant necropsy and PMCT findings.…”
Section: Introductionmentioning
confidence: 99%